Riboflavin Attenuates Influenza Virus Through Cytokine-Mediated Effects on the Diversity of the Gut Microbiota in MAIT Cell Deficiency Mice - Li, Ying; Shi, Chun-Wei; Zhang, Yu-Ting; Huang, Hai-Bin; Jiang, Yan-Long; Wang, Jian-Zhong; Cao, Xin; Wang, Nan; Zeng, Yan; Yang, Gui-Lian; Yang, Wen-Tao; Wang, Chun-Feng (Frontiers in Microbiology, 2022)
Influenza is a serious respiratory disease that continues to threaten global health. Mucosa-associated invariant T (MAIT) cells use T cell receptors (TCRs) that recognize microbial riboflavin-derived synthesis of intermediates presented by the major histocompatibility complex (MHC) class I-like protein MR1.Riboflavin synthesis is broadly conserved. Nevertheless, less-known roles or mechanisms of riboflavin in MR1-/- mouse influenza infection. In our study, immunofluorescence techniques were applied to analyze the number and distribution of viruses in lung tissue. Flow cytometry (FCM), ELISA and qPCR were applied to assess the amount of cytokine expression. Analysis of fecal flora changes in mice by amplicon sequences of the 16S V3-V4 region. Our study showed that MAIT cell deficiency increased mortality. Moreover, riboflavin changed these effects in microbiota-depleted mice. Oral administration of riboflavin inhibited IL-1β, IL-17A and IL-18 production but significantly increased IFN-γ, TNF-α, CCL2, CCL3 and CCL4 in a mouse model. Riboflavin treatment significantly increased the mouse flora relative abundance of Akkermansia and Lactobacillus (p <0.05) and decreased the content of Bacteroides. In contrast, MR1-/-mice exhibited a concentrated aggregation of Bacteroides (p <0.01), indicating that MAIT cell deficiency reduced the diversity of the bacterial population. Our results define MAIT cell function with riboflavin in resistance to influenza virus and suggest a potential role of riboflavin in enhancing MAIT cell immunity and intestinal flora diversity. Gut populations can be expanded to enhance host resistance to influenza, which represents a novel interaction among viruses, MAIT cells and gut microbiota.